2009
DOI: 10.1038/ajg.2009.437
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy and Overexpression of Ki67 and p53 as Markers for Neoplastic Progression in Barrett's Esophagus: A Case–Control Study

Abstract: p53 overexpression and, to a lesser extent, Ki67 overexpression could predict neoplastic progression in BE irrespective of the histological result. These markers may be useful for identifying patients at an increased risk of developing EAC, either alone or used as a panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 46 publications
3
67
0
2
Order By: Relevance
“…4 In response to shortcomings of the current clinical parameters used to manage BE and EAC, studies to identify novel biomarkers for BE and EAC have been in progress for several years. Previously evaluated markers discovered through these research efforts include aneuploidy and LOH, 4,11,18 p53 positivity [18][19][20] and EGFR levels. 21 There has also been recent interest in epigenetic alterations as biomarkers in BE and EAC, primarily in the form of DNA hypermethylation.…”
Section: Resultsmentioning
confidence: 99%
“…4 In response to shortcomings of the current clinical parameters used to manage BE and EAC, studies to identify novel biomarkers for BE and EAC have been in progress for several years. Previously evaluated markers discovered through these research efforts include aneuploidy and LOH, 4,11,18 p53 positivity [18][19][20] and EGFR levels. 21 There has also been recent interest in epigenetic alterations as biomarkers in BE and EAC, primarily in the form of DNA hypermethylation.…”
Section: Resultsmentioning
confidence: 99%
“…The study of Ki-67 in BE is pointed towards its probable prognostic role in combination with other factors, like chromosomic proteins and cyclin D1 [20,21]. Sikkema et al [32] found that increased expression of Ki-67 and protein p53 predicted progression to high-grade dysplasia and/or adenocarcinoma. Other studies underline the importance of the part of the epithelium that expresses Ki-67.…”
Section: Discussionmentioning
confidence: 98%
“…Methods that have been applied in published studies were minimally revised and used for the evaluation of COX-2 and Ki-67 expression [14,31,32]. The assessment was based on the percentage of positive metaplastic epithelia according to the following scale: no staining, mild (\20% positive epithelial cells), moderate (20-40% positive cells), and strong staining ([40% positive cells).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The p53 protein has been evaluated in stratifying LGD patients and found that the overexpression of the protein is associated with an increased risk of progression. [36][37][38][39] Kastelein et al showed that when combined with LGD aberrant p53 expression, defined as either an overexpression or complete loss of expression, became a powerful predictor of neoplastic progression (relative risk [RR] adjusted for age, gender, Barrett length 12.2; 95% CI 6.1-24.5; positive predictive value [PPV] 33%) with concomitant high interobserver agreement for LGD (κ = 0.79). 40 However, a prospective cohort study performed by Bani-Hani et al on 307 patients with BE found no significant changed odds of neoplastic progression with p53 overexpression (P = 0.197).…”
Section: Biomarkers In Lgdmentioning
confidence: 99%